On Robust Syndrome-Based Distributed Source Coding over Noisy Channels using LDPC Codes - Heidarzadeh, A.; Lahouti, F. (2007 IEEE International Conference on Signal Processing and Communications, 2007)
In this paper, we consider distributed source coding (DSC) problem over actual noisy channel addressed as distributed joint source-channel coding (DJSCC) while targeting the important applications of real-world transmission. Our objective is to design robust syndrome-based Slepian-Wolf decoding schemes guaranteeing both efficient distributed source compression and error protection. We utilize low-density parity-check (LDPC) codes and systematically design a decoder matrix based on the parity-check matrix of the encoder which is optimized for efficient decoding in DJSCC scenario.